Associations between sleep duration and cardiovascular diseases: A meta-review and meta-analysis of observational and Mendelian randomization studies - Wang, Shanshan; Li, Zhexi; Wang, Xiaoyu; Guo, Sheng; Sun, Yujing; Li, Guohua; Zhao, Chenhao; Yuan, Wenhui; Li, Meng; Li, Xiaolei; Ai, Sizhi (Frontiers in Cardiovascular Medicine, 2022)
The associations between sleep duration and cardiovascular diseases (CVDs) have been explored in many observational studies. However, the causality of sleep duration and many CVDs, such as coronary artery disease (CAD), heart failure (HF), and stroke, remains unclear. In the present study, we conducted a systematic meta-review and meta-analysis of the results of observational and Mendelian randomization (MR) studies to examine how sleep duration impact the risk of CVDs. We searched articles published in English and before September 10, 2021 in PubMed, Web of Science, and Embase. The articles were screened independently by two reviewers to minimize potential bias. We combined the meta-analyses of observational studies and 11 MR studies and summarized evidence of the effect of sleep duration on the risk of CAD, HF, stroke, and cardiovascular and all-cause mortality. Results showed that a) evidence is accumulating that short sleep duration is a causal risk factor for CAD and HF; b) abundant evidence from observational studies supports that long sleep duration is associated with the risk of CAD, stroke, and mortality, and long sleep duration has no causal associations with stroke and CAD in the MR studies; the causation of long sleep duration and other CVDs should be further studied; c) emerging evidence indicates that increase in hours of sleep is associated with decreased risk of CAD. Finally, we discussed the underlying pathophysiological mechanisms underlying short sleep duration and CVDs and suggested that increasing sleep duration benefits cardiovascular health.